2014
DOI: 10.1016/j.socscimed.2014.01.050
|View full text |Cite
|
Sign up to set email alerts
|

Very low birthweight: Dysregulated gestation versus evolutionary adaptation

Abstract: Much medical literature attributes persistently high rates of very low birthweight (VLBW) to “dysregulated” gestation. We offer the alternative view that natural selection conserved well-regulated, though nonconscious, decisional biology that protects the reproductive fitness of women by spontaneously aborting gestations that would otherwise yield frail infants, particularly small males. Modern obstetric practice, however, converts some fraction of these erstwhile spontaneous abortions into live births of very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…Our findings build on a connection noted between selection in utero and ‘portfolio theory’ (Catalano et al, 2014; Forbes, 2009; Kahneman & Tversky, 1979: Markowitz, 1952). This theory suggests that a mother has a portfolio of living and/or potential children among whom she must invest her limited time and energy.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our findings build on a connection noted between selection in utero and ‘portfolio theory’ (Catalano et al, 2014; Forbes, 2009; Kahneman & Tversky, 1979: Markowitz, 1952). This theory suggests that a mother has a portfolio of living and/or potential children among whom she must invest her limited time and energy.…”
Section: Discussionsupporting
confidence: 83%
“…Little literature has pondered whether risk aversion in the non-conscious decisional biology that ends or extends human gestation varies over time with risk aversion in conscious assessments that inform, for example, economic choices. One study reports that decreases in the self-reported willingness of households to assume financial risk predict increases in the incidence of low weight male births in Sweden (Catalano et al, 2014). The authors argue that the association arises because increasing risk aversion in decisional biology leads to spontaneous abortion of higher risk/lower reproductive return fetuses, but advanced medical technology ‘converts’ some fraction into live preterm, and therefore low weight, births.…”
mentioning
confidence: 99%
“…Logistic regression models were constructed in different quartiles to estimate the potential threshold effects. Previous studies have reported that different fetal sexes had different responses towards the environmental simulation in vivo and in vitro, suggesting that infant sex is related to the regulation of birth health (Al-Qaraghouli and Fang 2017; Catalano et al 2014; Challis et al 2013; Liu et al 2018). We also conducted analysis among male infants and female infants during different exposure windows to compare the variation between the different sexes.…”
Section: Introductionmentioning
confidence: 99%
“…Strategic parturition posits that natural selection has conserved decisional biology that protects the fitness of women and their offspring by controlling, without maternal awareness, the length of gestation. Under this narrative, the commonly reported association between, for example, stressful experiences and preterm birth arises, at least in part, not from the dysregulation of parturition but from the use of advanced obstetric procedures to “save” pregnancies that well‐regulated decisional biology would otherwise have terminated in spontaneous abortion, miscarriage, or stillbirth (Catalano et al, ).…”
mentioning
confidence: 99%